2010
DOI: 10.1134/s1063772910120024
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the circumbinary envelope around a young binary system

Abstract: The structure of a circumstellar envelope around a young binary T Tauri star is considered. The supersonic orbital motion of the system components in the envelope gas leads to the formation of bow shocks around the star. Two-and three-dimensional numerical modeling indicates an important role of these shocks in the formation of the structure of the circumbinary envelope. In particular, for systems with circular orbits, the size of the central region of the envelope that is not filled with matter (the gap) is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 16 publications
4
28
0
Order By: Relevance
“…The flow of matter in binary systems accreting material from protoplanetary disks has been simulated numerically in many studies [7][8][9][10][11][12][13][14][15][16][17]. The simulation results indicate the following major flow elements in these systems: circumstellar accretion disks around the system components, a rarefied area in the central parts of the protoplanetary disk adjoining the binary, and a complex system of gas-dynamical flows.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The flow of matter in binary systems accreting material from protoplanetary disks has been simulated numerically in many studies [7][8][9][10][11][12][13][14][15][16][17]. The simulation results indicate the following major flow elements in these systems: circumstellar accretion disks around the system components, a rarefied area in the central parts of the protoplanetary disk adjoining the binary, and a complex system of gas-dynamical flows.…”
Section: Introductionmentioning
confidence: 99%
“…For reverse rotation to occur, the angular momentum delivered to the disk by the falling matter must be opposite to the angular momentum of the system. Numerical simulations of these systems have been performed in various studies [7][8][9][10][11][12][13][14][15][16][17], have not indicated the appearance of reversed accretion disks in binary systems for a wide range of parameters. In addition, analysis of the flow structure that forms in the vicinity of a young binary indicates that flows directed opposite to the motion of the components can exist [15].…”
Section: A Model For the Formation Of A Reversed Accretion Diskmentioning
confidence: 99%
See 1 more Smart Citation
“…They come in two flavors: First, the systems where at least one component of the binary hosts a circumstellar disks, as studied by Regály et al (2011a,b); and second, binaries with a circumbinary disk (e.g., GG tau, Piétu et al 2011;V4046 Sgr., Rodriguez et al 2010). In the second case (circumbinary disks), the orbital motion of the central binary is predicted to induce periodic perturbations, spiral density waves, and gas flows in the disk (Artymowicz & Lubow 1996;Larwood & Papaloizou 1997;Günther & Kley 2002;Günther et al 2004;Sotnikova & Grinin 2007;Hanawa et al 2010;Kaigorodov et al 2010;Alexander 2012;de Val-Borro et al 2011;Kocsis et al 2012). Characteristic features resulting from this interaction are inner cavities with the radius of about twice the semi-major axis of the binary (e.g., Artymowicz & Lubow 1994;Günther & Kley 2002).…”
Section: Introductionmentioning
confidence: 99%
“…
We have carried out 2D and 3D numerical simulations (Kaigorodov et al 2010 of accretion processes in binary T Tauri stars (TTSs) DQ Tau, UZ Tau E, V4046 Sgr, GW Ori, RoXs 42C using a finite-difference Roe-Osher-Einfeld TVD scheme. The morphology of the flow pattern for UZ Tau E is shown in Fig.
…”
mentioning
confidence: 99%